Análisis de la relación entre la ejecución de ingresos y la ejecución de gastos en la Municipalidad Provincial de Maynas 2015-2023 - Paredes Portocarrero, Russel Herless (2024)
The present research is quantitative, correlational level and non-experimental design with longitudinal data. The study population included the quarterly data on the amounts of income collected and expenses accrued in the Provincial Municipality of Maynas 2015-2023. The main purpose was to analyze the relationship between the variables under study. The results achieved, through the application of Spearman's Rho correlation coefficient for non-parametric data at the 90% confidence level, demonstrate that there is a positive relationship of 33.23% between the evolution of the execution of income and expenses in the institution. After classifying the income according to the sources of financing, it was determined that the execution of expenses does present a relationship with the execution of income from specific resources, but it does not present a relationship with the execution of income from resources directly collected.